2019
DOI: 10.1101/2019.12.14.876474
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative analysis of the plasma proteome and polygenic risk of cardiometabolic diseases

Abstract: Polygenic risk scores (PRSs) capture the polygenic architecture of common diseases by aggregating genome-wide genetic variation into a single score that reflects individual's disease risk, affording a new opportunity to identify downstream molecular pathways involved in disease pathogenesis. We performed an integrative analysis to characterise associations of PRSs of five cardiometabolic diseases with 3,442 plasma proteins in 3,175 healthy individuals. Through polygenic association scans we identified 48 plasm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 122 publications
1
10
0
Order By: Relevance
“…Our findings support a model where higher protein expression of the BCAA catabolic pathway reduces risk of type 2 diabetes. Another interesting causal candidate is WFIKKN2, also supported by a recent MR study using the same outcome data as here but different instruments ( 43 ). WFIKKN2 is a follistatin domain–containing protein that binds GDF8/GDF11 proteins with high affinity ( 46 )—both of which have been implicated in diabetes ( 47 , 48 ).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our findings support a model where higher protein expression of the BCAA catabolic pathway reduces risk of type 2 diabetes. Another interesting causal candidate is WFIKKN2, also supported by a recent MR study using the same outcome data as here but different instruments ( 43 ). WFIKKN2 is a follistatin domain–containing protein that binds GDF8/GDF11 proteins with high affinity ( 46 )—both of which have been implicated in diabetes ( 47 , 48 ).…”
Section: Discussionsupporting
confidence: 74%
“…As this was the case even when we considered observational estimates for incident type 2 diabetes (thus, protein changes occurring before the onset of disease), these results may suggest that the genetic liability to type 2 diabetes, and the related physiological changes that may develop before overt disease, already have an effect on these proteins and that those effects may be greater than the effects of the proteins themselves on the disease. Others have furthermore suggested that an effect of a disease polygenic risk score on gene or protein levels may represent convergent genetic effects on important disease pathways ( 42 , 43 ). Further work is needed to establish the complex causal chain from individual proteins to convergent pathways, intermediate phenotypes, and overt type 2 diabetes, which may then in turn affect serum protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Polygenic scores based on disease variants have been alternatively used to identify disease-mediating candidate proteins. Ritchie et al [88] evaluated the influence of genetic predisposition to complex diseases on the plasma proteome, identifying 48 proteins whose levels were modulated by polygenic scores for coronary artery disease, chronic kidney disease, and T2D. A large proportion of pQTLs (Emilsson V. et al [83] report 60% of their discovery set) overlap with known disease-associated loci identified through GWAS, suggesting a common causal variant.…”
Section: Beyond Prediction: Integration Of Genomics and Proteomics Tomentioning
confidence: 99%
“…A large proportion of pQTLs (Emilsson V. et al [83] report 60% of their discovery set) overlap with known disease-associated loci identified through GWAS, suggesting a common causal variant. However, in most cases where pQTLs overlap with variants composing disease GRSs (or with variants in high LD), associations were largely driven by polygenic effects rather than by these overlapping single loci [88].…”
Section: Beyond Prediction: Integration Of Genomics and Proteomics Tomentioning
confidence: 99%
“…MR has also been used to determine whether a genetic susceptibility to certain chronic diseases in uences other biological traits such as the blood proteome or the blood metabolome. 23,24 Here, we performed a meta-analysis of electronic health record (EHR)-based genome-wide association studies (GWAS) to identify genetic variants robustly associated with NAFLD. We then used a MR study design to identify novel blood proteins/metabolites causally associated with NAFLD.…”
Section: Introductionmentioning
confidence: 99%